Enzyme-based DNA extraction from zoospores of ruminal fungi - K.-P. Tsai; R. E. Calza (Fungal Genetics Reports, 1992)
We report here a rapid, efficient and simple method for the extraction of high molecular weight DNA from zoospores of Neocallimastix frontalis EB188. This anaerobic fungus, isolated from bovine digesta, effectively degrades plant fiber in vitro (Barichievich et al. 1990. Appl. Env. Micro. 56:43-48). Our interest in ruminal fungi stems from their ability to degrade wood materials (Joblin et al. 1989. FEMS Micro. Lett. 56:119-122) and their potential use in biomass saccharification. Zoospore DNA synthesis is of particular interest to our laboratory. It is these motile zoospores which colonize and degrade plant materials (Mountfort 1987. FEMS Micro. Rev. 46:501-508). To detail fully this metabolic event, it will be necessary to extract nucleic acids from zoospores. Such procedures have not been reported in the literature. Using acetone drying and enzymatic removal of cell walls, we have isolated high molecular weight DNA from very small amounts of culture. The procedure takes less than one hour and DNA yields are high. The DNA is readily cut with restriction endonucleases and religated efficiently but is otherwise stable. Electrophoretic analysis of the DNA confirmed the presence of repetitive sequences. This procedure will aid the study of DNA replication, DNA repair and DNA RFLP analysis of various strains using small (<1 ml) cultures.